Next Generation Sequencing Identify Rare Copy Number Variants in Non-syndromic Patent Ductus Arteriosus - Chen, Bo; Hou, Aiping; Zhao, Lin; Liu, Ying; Shi, Xin; Du, Bowen; Yu, Yu; Zhao, Pengjun; Gao, Ying (Frontiers in Genetics, 2020)
Patent ductus arteriosus (PDA) is a common congenital cardiovascular malformation with both inherited and acquired causes. Several genes have been reported to be related to PDA, but the molecular pathogenesis is still unclear. Here, we screened a population matched cohort of 39 patients with PDA and 100 healthy children using whole exome sequencing (WES). And identified 10 copy number variants (CNVs) and 20 candidate genes using Gene ontology (GO) functional enrichment analysis. In gene network analysis, we screened 7 pathogenic CNVs of 10 candidate genes (MAP3K1, MYC, VAV2, WDR5, RXRA, APLNR, TJP1, ERCC2, FOSB, CHRNA4). Further analysis of transcriptome array showed that 7 candidate genes (MAP3K1, MYC, VAV2, APLNR, TJP1, FOSB, CHRNA4) were indeed significantly expressed in human embryonic heart. Moreover, CHRNA4 was observed the most important genes. Our data provided rare CNVs as potential genetic cause of PDA in humans and also advance understanding of the genetic components of PDA.